The Psychosocial Impact Of Sexual Violence On Santri In Religious Education Institutions - Giyantoro, Eko Giyantoro; Sukidin; Pudjo Suharso (Profesional Muda Cendekia Publishing, 2024)
Research Aims: This study aims to understand how sexual violence affects the psychological and social conditions of santri in religious education institutions in Singojuruh sub-district, Banyuwangi Regency. Design/methodology/approach: This study uses a qualitative approach with a phenomenological design to explore the experiences, perceptions, and psychosocial impacts of violence on santri in religious education institutions. Data were collected through in-depth interviews and participatory observation with a number of santri, ustadz, psychologists, and the community. Data were analysed thematically to identify main patterns, key findings, and perspectives that emerged from participants' narratives. Research Findings: This study shows that victims experience deep trauma that affects their mental and emotional well-being. The violence also resulted in prolonged fear, shame, and low self-esteem, as well as psychological disorders such as depression and anxiety. Sexual violence also has a negative impact on academic achievement and social participation, hindering students' personal and educational development. Theoretical Contribution/Originality: This research argues for its originality in analysing in depth the specific psychosocial impact of sexual violence on santri, with a focus on religious education institutions, which has not been widely explored in the context of academic literature on sexual trauma and religious education environments in Indonesia.